Perilaku Mencari Polen dan Identifikasi Polen Tetragonula laeviceps pada dua Kebun Tanaman Obat - Agung Prasetyo; Rika Raffiudin; Irmanida Batubara; Nunik Sri Ariyanti (Institut Pertanian Bogor, 2022)
Unit Konservasi Budidaya Biofarmaka (UKBB) and Kampoeng Djamoe Organik Martha Tilaar (KaDO) are two medicinal plantation that possibly as resources for stingless bees nectar and pollen. This study was aimed to describe the foraging behavior of Tetragonula laeviceps in medicinal plantations, determine the plant species which become the pollen resources, and the distance between the colony and medicinal plants. Observation on foraging behavior were divided into three activities, i.e. flying out from the nest, returning the nest with pollen, and returning the nest without pollen. We found a similar pattern of numbers of bees returning to the nest with pollen in both UKBB and KaDO that occurred in the morning with the highest between 9 and 10 am and gradually decreased in the afternoon. The bees in UKBB showed highly number flying out from the nest in around 3 pm which might be the activites of resin collection. We identified 11 and 16 pollen types at the UKBB and the KaDO, respectively. The pollen in both locations are from the families Amaryllidaceae, Anacardiaceae, Clusiaceae, Cucurbitaceae, Ebenaceae, and Sapindaceae. Our results revealed that the distance range of medicinal plants from the bees hives was 13.4-113,3 m. Thus, this data indicate that the hives should be located in the distance of the bee forage. The medicinal pollen identified in the T. laeviceps pollen pot confirmed the role of the bees as the ecosystem service in the medicinal plantations. Keywords: foraging range, medicinal plants, pollination, pollen, Tetragonula